Endocrine aspects of anovulation - Jacobs, H. S. (1975)
Endocrine features of anovulation are reviewed, with particular emphasis on methods of investigation. The value of, and indications for, measurements of serum gonadotrophin concentrations are discussed: it appears that FSH measurements allow better discrimination than LH measurements in diagnosing patients with primary ovarian failure. The results of stimulation tests with the synthetic form of gonadotrophin-releasing hormone are described and the relationship of tests with exogenous progestogens and clomiphene is discussed.